Pemanfaatan Tanah, Kompos, dan Arang Sekam Untuk Pertumbuhan Tanaman Cabai - Faizah Mahi faizah; Rosmiati rosmiati; Herawaty herawaty; Aswar aswar; Nurul Mukhlishah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Chilis are a kind of plant that are established in a mass amount by Indonesian farmers and are believed to give a lot of benefits to health. However, its growth are not guaranteed to be ideal. One of the common problems in chilis’ growth is the inoptimality of the land’s yield. This is caused by the plants’ being not fertile because of weed growing around the plant, insufficient nutrients for the plants to keep its ideal growth, or the soil being contaminated by pollution such as detergents and excess chemical land fertilizer. The activity has been carried out April 9, 2022. Hence, the writer performed a counseling and training to a group of farmers incorporated in Lorong Cokonuri Farmers Group, Gunung Sari, Rappocini, Makassar City. The result showed an increase in the farmers’ knowledge and capability to grow the plant. In the future, this research is hoped to bring more improvement in the chili plants’ establishment.